2018
DOI: 10.3390/su10020377
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Support Intentions and Behaviors Regarding Urban Trees Programs: A Structural Equation Modeling-Multi Group Analysis

Abstract: Urban trees are more about people than trees. Urban trees programs need public support and engagement, from the intentions to support to implement actions in supporting the programs. Built upon the theory of planned behavior and Structural Equation Modeling (SEM), this study uses Beijing as a case study to investigate how subjective norm (cognition of urban trees), attitude (benefits residents' believe urban trees can provide), and perceived behavioral control (the believed ability of what residents can do) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…That is, the pay intention for conserving urban trees is influenced the most by residents' belief in their financial resources or capability, secondly by people of importance around them, and lastly by both understanding about urban tree usefulness and attitude to protect urban trees. Former studies point out that perceived behavioral control is the main factor that affects behavioral intention (Wan and Shen, 2015;Zhao et al, 2018). There is also other research suggesting attitude has a relatively small impact on behavioral intention [33,70].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That is, the pay intention for conserving urban trees is influenced the most by residents' belief in their financial resources or capability, secondly by people of importance around them, and lastly by both understanding about urban tree usefulness and attitude to protect urban trees. Former studies point out that perceived behavioral control is the main factor that affects behavioral intention (Wan and Shen, 2015;Zhao et al, 2018). There is also other research suggesting attitude has a relatively small impact on behavioral intention [33,70].…”
Section: Discussionmentioning
confidence: 99%
“…In the light of considerable research on environmental resource protection, it has been confirmed that those embracing support from families and companions (subjective norms), with a positive attitude (attitude) and believing in one's own ability to participate (perceived behavioral control), were positively and significantly related to behavior intention [18,[22][23][24][25][26]. Therefore, this study hypothesized that residents' subjective norm, attitudes toward conserving urban trees, and perceived behavioral control would have a significant effect on their behavioral intention to pay to conserve urban trees.…”
Section: The Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding items about residents’ attitudes, these were developed from the contributions of Ouyang et al (2017) and Woosnam et al (2018). Finally, for the elaboration of the items on residents’ intention to support (dependent variable), the studies of Bakhsh et al (2018) and Zhao et al (2018) were used.…”
Section: Methodsmentioning
confidence: 99%